Increasing the Growth and Yield of Tomato Plants (Lycopersicum esculentum Mill.) by Providing Potassium and Paclobutrazol - Nora Zubaidi; Djarwatiningsih; Agus Sulistyono (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Tomatoes (Lycopersicum esculentum Mill.) are a horticultural commodity with high economic value, but theirproductivity is often hampered by flower and fruit loss. Increasing growth and yield can be achieved throughpotassium fertilization, which plays a role in photosynthesis and fruit formation, and through the application ofthe growth regulator paclobutrazol, which suppresses vegetative growth and stimulates the generative phase. Thisstudy aims to evaluate the effects of potassium fertilizer dose and paclobutrazol concentration, and theirinteractions, on tomato growth and yield. The study was conducted in Surabaya from November 2024 to February2025 using a factorial Randomized Block Design with two factors: potassium fertilizer doses (110, 125, 140, 155kg/ha) and paclobutrazol concentrations (0, 100, 125, 150 ppm), each factor repeated three times. The resultsshowed that the combination of 140 kg/ha potassium fertilizer and 125 ppm paclobutrazol produced the highestnumber of leaves (37), number of bunches (6.78), total number of fruits (37.67), and total fruit weight per plant(1,509.27 g). Potassium fertilizer at 140 kg/ha alone produced the highest number of flowers (69.41), whilepaclobutrazol at 125 ppm accelerated flower emergence (34.53 days), increased the number of flowers (69.77),and increased fruit weight per harvest period. Thus, using 140 kg/ha of potassium fertilizer combined with 125ppm paclobutrazol is recommended as the most effective treatment to optimize tomato plant growth and yield.